Reminių lietuvių kalbos pagrindinių sakinio dalių perteikimas norvegų kalboje - Griškevičienė, Aurelija (Kalbotyra, 2008)
In Norwegian, like in other analytical languages, the distribution of information in terms of Functional Sentence Perspective (FSP) is heavily constrained by the grammatically defined word order, whereas the main means of expression of FSP in written Lithuanian is the word order, which is grammatically unrestricted thus enabling to convey the new information by any sentence part. The aim of this article is to summarise and classify expressions of Norwegian equivalents to the rhemic subject and predicate in the Lithuanian language. The analysis resorts for illustrations to the short story “Gyvenimas po klevu” by Granauskas and its translation into Norwegian. The analysis shows, one of the best ways to shift the rhemic from the usual position at the beginning of a sentence in the Norwegian language is by applying the passive voice. The subject can equally be made rhemic by the cleft, presentative construction, the reduplication of a sentence part. The subject rhemisation can happen by replacing it with other sentence parts of the same meaning. To retain the rhemic subject in translation, not only can a word order be reshuffled, but even an extra sentence added to convey new information. In Norwegian, the predicate has a strictly defined second position. Therefore, the rhemic predicate is impossible to indicate by a word order. In Norwegian sentences where new information is presented through the predicate, the position of the predicate is considered rhemic, and no other means to express the rhemic predicated are employed. In translation, the rhemic predicate can be expressed through the nominalization, which facilitates the needed shift. As the empiric material demonstrates, the predicate replacement by any other sentence part is the most frequent way for the rhemisation of the predicate. It is also possible to make verb-for-verb replacement. In certain cases, extra themic elements, helping to shift the focus predicate. The use of lexical means, to express the rheme is similar in both languages. The exeption is the expression of negation, which may have occasional differences. Both languages display the principle of the end position of the rheme with an exeption of cases of inversion, which is not rare in the text of fiction, as it tries to convey the stylisation of spoken language. Unfortunately, not all the available means of expression of FSP are employed in the translation, which leads to occasional distortions of the source information. Its importance should be given a higher degree of consideration.